Pelatihan Pembuatan Diagram dengan Microsoft Excel di SMP Mainang Kabupaten Alor - Narita Yuri Adrianingsih; Jeni Marianti Loban; Landerius Maro; Lory Fitriana Ur Dollu (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Diagram making training using Microsoft Excel is a community service carried out at the Toyg State Junior High School, which is in the Toyg Village, Alor Regency. This activity was carried out for 1 day during the training. This training aims to make students understand how to present diagrams using Microsoft Excel. The material provided has been prepared before the training, namely regarding the presentation of data with diagrams in the statistics subject. The method used is presentation and then direct practice is carried out by students. The obstacle at school is that there are no computer facilities so this is a new thing for them and they are very enthusiastic about participating in this training, so that the children quickly understand what they are being trained to do.